PROBLEMS OF QUALIFICATION OF CORRUPTION CRIMES COMMITTED IN THE FIELD OF PUBLIC PROCUREMENT - Кодиркулов Ахмаджон Адхамович (European Science Publishing, 2024)
This scientific article analyzes the problems of qualification of corruption crimes committed in the field of public procurement. The author initially divides the legal methods of combating corruption into two groups - preventive and punitive measures. The article lists the subjects of corruption crimes, including officials, employees of regulatory bodies, civil servants and others is characterized by direct intent and malicious interests. The author lists the main stages of the public procurement process and analyzes the crimes that can be committed at each stage. In particular, bribery, abuse of office, fraud and other crimes were considered. The article classifies corruption crimes into four groups: 1) directly directed against public service; 2) directed against an additional object; 3) directed against an optional object; 4) crimes directed against a similar object. In the article, the author analyzes in detail the objective, subjective and subject of corruption crimes. The final part lists the main features of corruption crimes in the field of public procurement and emphasizes the need to improve law enforcement practice.
Keywords: public procurement, corruption, qualification of crime, official, bribery, abuse of power, object of crime, subject of crime, objective side of crime, subjective side of crime.